Determining Reorder Points When Demand is Lumpy - Ward, J. B. (Management Science, 1978)
Lumpy or sporadic demand patterns with highly skewed distributions are common in parts and supplies types of stockholdings, and much of available inventory control methodology is not appropriate for such items. This paper presents a simple, easily used regression model to calculate order points for lumpy items from knowledge of demand parameters and the desired service level. It is derived from the particular compound Poisson distribution commonly called “stuttering Poisson.” Results are derived and presented in the following framework, though application is not limited to these conditions. The control discipline is the order quantity, order point (Q, R) approach with continuous review. Lead time is assumed to be known and constant. An assigned service level is assumed based on fraction of demand supplied without backorder. Joint optimization of Q and R is not addressed, but rather order point is based on an independently calculated order quantity. Forecasting methods are not addressed, but the mean and variance of lead time demand forecasts are assumed available.